Bridging the Theories of Affordances and Limb Apraxia - Ferdinand Binkofski (Frontiers Research Topics, 2017)
Affordances are meaningful relations between the features of observed objects and the observer's action systems with its proper abilities. The notion of affordance integrates perceptual, cognitive and motor functions, so that perceiving an object, conducting cognitive operations on it, and executing motor actions with it cannot be considered as independent functions. Limb apraxia is a higher-order motor disorder that refers to disturbance of one or more of three domains: imitation of meaningless gestures, pantomime of meaningful gestures, and disturbance of interaction with objects. The first aim of the Research Topic was to put together theoretical and research contributions on affordance mechanisms to highlight their role in explaining apraxia deficits. The second aim was to clarify how studies on apraxia have implications for theories of affordances.